Synthesizing Embodied Tourist Experience with Indigenous Epistemology: A Grounded Theory Approach to Sustainable Surf Tourism Development at Parangtritis - Nurdina Prasetyo; Pranoto Pranoto; Sukrisno Sukrisno; Gana Wuntu; Haniek listyorini (UNIVED Press, 2026)
ABSTRACT This study addresses theoretical fragmentation in surf tourism scholarship through systematic integration of embodied experience theory, sustainable livelihood frameworks, and indigenous knowledge systems. A comprehensive theoretical model was developed synthesizing affective tourist dimensions with indigenous epistemology in community based sustainable surf tourism management at Parangtritis Beach, Yogyakarta, Indonesia. Grounded theory methodology guided six month ethnographic fieldwork comprising semi structured interviews, focus group discussions, participant observation, and documentary analysis with diverse stakeholders including domestic and international surfers, instructors, community leaders, and destination managers. Three stage coding procedures utilizing MAXQDA2020 achieved theoretical saturation through rigorous data triangulation, member checking, and peer debriefing protocols. Analysis yielded the SEMO (Sensory Emotional Mystical Oneness) model, a substantive theoretical framework explicating how sensory engagement, emotional responses, mystical cultural dimensions rooted in Nyi Roro Kidul cosmology, and ecological oneness converge to constitute transformative surf tourism experiences while advancing local sustainability objectives. This investigation provides the inaugural theoretical integration of embodied experience with Indonesian indigenous epistemology in adventure tourism contexts, extending extant frameworks through incorporation of mystical spiritual dimensions heretofore absent from surf tourism scholarship. The SEMO model furnishes novel analytical perspectives for destination management that simultaneously optimize experiential quality and preserve Javanese cultural heritage, thereby bridging adventure tourism development imperatives with ecosystem sustainability through indigenous knowledge valorization. Keywords: surf tourism, sustainable livelihood, embodied experience, indigenous knowledge, SEMO model, Parangtritis Beach